Comparing Melanoma Invasiveness in Dermatologist- versus Patient-Detected Lesions: A Retrospective Chart Review - Cindy L. Lamerson; Kristina Eaton; Joel L. Sax; Mohammed Kashani-Sabet (Journal of Skin Cancer)
This study examined whether patient-identified melanomas were more advanced than dermatologist-identified tumors at routine clinic visits, and whether a personal or family history of skin cancer was associated with patterns of detection. A retrospective chart review was performed on melanoma patients (N=201) in a private dermatology clinic. Variables included age, gender, pattern of detection (i.e., patient or a board certified dermatologist), personal or family history of skin cancer, skin type, and previous sun exposure, as well as tumor location and severity. Dermatologist-diagnosed melanomas were less invasive (P<0.0005), and more likely present on the chest, back, and legs (P<0.01). Conversely, patient-identified lesions were more likely to occur on the face, neck and scalp, be associated with younger patients, and a family history of melanoma, but not other types of skin cancer (P<0.01). In a post-hoc analysis examining these factors as predictors of tumor invasiveness, only diagnostic source was significant. Specifically, dermatologist-identified tumors were significantly less invasive than patient-identified tumors. Although age, family history, and tumor location played roles in the early detection of melanomas, the most important factor was diagnostic source. Thus, board-certified dermatologists play a key role in the early detection of malignant melanoma.